A 116‐Nuclear Metallosupramolecular Cage‐of‐Cage Showing Multistep Single‐Crystal‐to‐Single‐Crystal Transformation. Issue 8 (28th January 2020) - Imanishi, Kento; Wahyudianto, Benny; Kojima, Tatsuhiro; Yoshinari, Nobuto; Konno, Takumi
Abstract: Here a unique single‐crystal‐to‐single‐crystal (SCSC) transformation of a 116‐nuclear Au I 72 Cd II 40 Na I 4 cage‐of‐cage (2 CdNa ) is reported, which was created from a trigold(I) metalloligand with d ‐penicillamine by way of a 9‐nuclear Au I 6 Cd II 3 cage (1 ). Cage‐of‐cage 2 CdNa is composed of 12 cages of 1 that are linked by 4 Cd 2+ and 4 Na + ions, with its surface being covered by 12 NO3 − ions to form a discrete, spherical molecule with a diameter ca. 4.7 nm. In crystal 2 CdNa, the cage‐of‐cage molecules are packed in a cubic lattice with a huge cell volume of ca. 4.5×10 5  Å 3, so as to have large interstices with diameters of more than 3 nm. Upon soaking crystals 2 CdNa in aqueous Cu(NO3 )2, all Cd 2+ and Na + were quickly exchanged by Cu 2+ to produce an analogous Au I 72 Cu II 44 cage‐of‐cage (2 Cu ) in a SCSC manner. Prolonged soaking led to the SCSC transformation to another supramolecular structure (2′ Cu ) consisting of 152‐nuclear Au I 72 Cu II 80 cage‐of‐cages that are alternately H‐bonded with the Au I 72 Cu II 44 cage‐of‐cages. 2′ Cu showed the accommodation of MoO4 2− and the conversion of MoO4 2− to β‐Mo8 O26 4− in the crystal, with retention of single‐crystallinity. Abstract : Cage in : A 116‐nuclear Au I 72 Cd II 40 Na I 4 cage‐of‐cage with a diameter of 4.7 nm was newly synthesized and crystallized by way of a 9‐nuclear Au I 6 Cd II 3 cage. On soaking its crystals in aqueous Cu 2+, all Cd 2+ and Na + ions in the cage‐of‐cage were quickly exchanged by Cu 2+ ions in a SCSC manner to produce an analogous Au I 72 Cu II 44 cage‐of‐cage, which was further SCSC converted to a 152‐nuclear Au I 72 Cu II 80 cage‐of‐cage.